GAMBARAN KELELAHAN KERJA PADA SOPIR BUS RAPID TRANSIT DI TRANS METRO DEWATA BALI TAHUN 2023 - Kusumadewi, Ni Nyoman Asvini; Duana, I Made Kerta (ARCHIVE OF COMMUNITY HEALTH; Vol 12 No 1 (2025): April 2025, 2025)
ABSTRACT Bus Rapid Transit (BRT) is a high-quality bus-based transportation that offers comfort, safety, punctuality, good infrastructure, and a scheduled system. Factors that cause traffic accidents include human error, mechanical failure, road conditions and situations, and weather factors. According to the Ministry of Transportation of the Republic of Indonesia, human factors dominate the causes of traffic accidents, where driver fatigue is the leading cause of accidents. This study aims to determine the description of work fatigue among bus rapid transit drivers at Trans Metro Dewata Bali in 2023. This research is quantitative descriptive research with a cross-sectional study approach. The research location is in the Trans Metro Dewata Bali Bus Corridor.The minimum sample size is 78 samples obtained by non-probability sampling technique with a consecutive sampling approach. Data was collected by in-person interviews using respondent's questionnaire and the KAUPK2 questionnaire to measure work fatigue. Data analysis used univariate analysis and cross-tabulation analysis. The results showed that most of the rapid transit bus drivers on the Trans Metro Dewata Bali in 2023 had a level of work fatigue in the tired category of 39 people (48.8%). Companies are expected to provide information related to occupational health and safety, especially work fatigue. Keywords: Bus Rapid Transit, Driver, Work Fatigue